A Case Report on Aggressive Breast Cancer - Rayamajhi, Kundana; Ghimire, Ram Kumar; Kayastha, Bhuwan (Nepalese Journal of Radiology, 2023)
Human epidermal growth factor receptor-2 (HER 2) positive breast cancers represent a highly aggressive breast cancer subtype and are associated witha worse prognosis. They tend to be more aggressive with lower survival rates but with  a better prognosis than the triple-negative subtype.